Exploring the Dimensions of Spirituality, Wellness and Value Creation amidst Himalayan Regions Promoting Entrepreneurship and Sustainability - Manpreet Arora; Vaishali Dhiman; Roshan Lal Sharma (Journal of Tourismology)
Spirituality and wellness are intertwined in Himalayan regions with each other.We can find a unique blend of spiritual traditions as well as healing practices in these regions. The experiences of tourists in Himalayan regions are very profound and transformative in various aspects. In order to seek spiritual solace and blessings, various travelers undertake pilgrimages to in these regions to various sites, temples, monasteries and routes. The intersection of spirituality, wellness, value creation, entrepreneurship, and sustainability in the Himalayan regions can have several implications. The findings highlight that the Himalayan highlands are regarded as being serene, beautiful natural areas for spiritual retreats. There is an emphasis on holistic well-being that goes beyond financial considerations by highlighting wellness and spirituality in entrepreneurial and environmental activities. In the Himalayan areas, integrating spirituality, wellness, and sustainability can encourage and support entrepreneurship. An innovative and creative attitude can be encouraged by placing a strong emphasis on values, awareness, and connectivity.